Rural wealth creation of intellectual capital from urban local food system initiatives: Developing indicators to assess change. Issue 5 (20th October 2017) - Schmit, Todd M.; Jablonski, Becca B. R.; Minner, Jennifer; Kay, David; Christensen, Libby
Abstract: With growing interest in wealth creation in rural areas from farmer participation in urban local food markets, defining empirical measures is crucial. However, data limitations and a lack of agreement on what serves as reasonable proxies for alternative capital measures makes the process challenging. Using the Delphi Method and considering a large urban farmers market system, this study prioritizes impacts on eight forms of community capital and estimates empirically flows of intellectual capital to rural areas using primary data from market vendors and customers. Results indicate that sufficient engagement between farmers and urban consumers, combined with educational programming by the farmers market, can increase the transmission of intellectual capital flows to rural areas. For the large urban-based farmers market evaluated, we find that such participation is associated with higher human capital stocks in the counties in which the farmers reside.